Description of Hemoglobin and Erythrocyte Levels in Tuberculosis Patients at Prof. Dr. HM Anwar Makkatutu Regional Hospital, Bantaeng Regency - Dewi B , Ade Risma Zagina; Islawati, Islawati; Asdinar; Asnidar (Frontiers in Sustainable Science and Technology, 2025)
Data from the World Health Organization (WHO) in 2023, tuberculosis (TB) is a long-standing disease. The relationship between hemoglobin levels in tuberculosis, decreased hemoglobin levels in tuberculosis sufferers can be caused by the tuberculosis infection process. Bad habits such as staying up late, smoking, consuming alcohol, and unmet nutritional needs. While the relationship between erythrocyte levels in tuberculosis can affect all hematopoiesis series, especially in erythrocytes, when erythrocytes are infected, a reaction will occur where the life mass of erythrocytes is shortened by around 10-20 days, while in normal conditions the life mass of erythrocytes is 120 days. This research is a type of quantitative research with a descriptive research design using purposive sampling techniques. Based on the results of the study on the description of hemoglobin and erythrocyte levels in inpatients with tuberculosis at Prof. Dr. HM Anwar Makkatutu Regional Hospital, Bantaeng Regency, it was found that out of 250 samples of pulmonary tuberculosis patients, it showed that patients with predominantly normal hemoglobin and erythrocyte levels were 155 (62%) people, while patients with low hemoglobin and erythrocyte levels were 95 (38%) people.